Incidental 99mTc-HDP Uptake in a Dominant Thyroid Nodule on Bone Scan. (May 2017) - Shetty, Deepa; Yung, Grace; Russo, Roberto; Mansberg, Robert
Abstract : Abstract: A 67-year-old woman was referred for a bone scan for evaluation of increasing serum alkaline phosphatase levels. Bone scan revealed no abnormal uptake in the skeleton. However, intense hypervascularity and delayed tracer uptake were incidentally identified in an enlarged right thyroid gland. A thyroid scintigraphy, contrast-enhanced CT of the neck, and sonographic evaluation of the abnormality were subsequently organized to characterize the lesion. An ultrasound-guided fine-needle aspiration revealed a benign follicular pattern (Bethesda II), and histopathology of the right hemithyroidectomy confirmed a dominant nodule within a nodular goiter.